2015
DOI: 10.1007/s00404-015-3852-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum folate level and cervical cancer: a meta-analysis

Abstract: Based on our meta-analysis, deficiency of serum folate level was associated with the increased risk of cervical cancer among Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…The mechanism by which malignancy causes macrocytosis is unknown, as are the mechanisms of many other causes of macrocytosis. Some studies have implied that there exists an association between reduced folate status and an increased risk of malignancy [25,26]; however, in our study, the presence of folate deficiency was unlikely because of each medical record and because of the pattern of histograms. Recently, Yokoyama and others examined the MCV of Japanese alcoholic men with (n = 65) and without (n = 206) esophageal squamous cell carcinomas.…”
Section: Discussioncontrasting
confidence: 66%
“…The mechanism by which malignancy causes macrocytosis is unknown, as are the mechanisms of many other causes of macrocytosis. Some studies have implied that there exists an association between reduced folate status and an increased risk of malignancy [25,26]; however, in our study, the presence of folate deficiency was unlikely because of each medical record and because of the pattern of histograms. Recently, Yokoyama and others examined the MCV of Japanese alcoholic men with (n = 65) and without (n = 206) esophageal squamous cell carcinomas.…”
Section: Discussioncontrasting
confidence: 66%
“…Particularly, fruit and vegetable consumption, as well as intake of nutrients (i.e. vitamins A, C, and E, folates, carotenoids, and minerals), have been associated with reduced risk of HPV infection, CIN and CC [6][7][8][9][10][11][12][13][14]. These findings support the role of vitamins as protective nutrients against CC, via inhibiting cancer cell proliferation [15], stabilizing p53 [16], preventing DNA damage and reducing immune-suppression [15,17].…”
Section: Introductionmentioning
confidence: 77%
“… 16 for gastric (3 prospective, 13 retrospective) 4,414/209,689 Lin HL [ 22 ] 13 studies with 14 estimates (7 cohort, 6 case-control); 5 supplemental N = 3,467 Pancreatic Serum folate NS: decreased risk Folic acid supplementation S: decreased risk for 100 mcg/day increment increase intake Wang R [ 24 ] 10 studies. n = 202,517 Prostate Serum folate S: high levels serum folate levels were associated with increased risk 5 nested case-control Dose-response S: 5 nmol/L increment associated with increased risk Tio M [ 17 ] 7 (6 nested case-control, 1 case-control) 6,122/10,232 Prostate Serum folate S: high levels associated with increased risk Zhou X [ 28 ] 6 case-control 873/1,510 Cervical Serum folate S: deficient serum folate levels and increased risk; S: increased risk if folate level ≤ 6.4 ng/ml; NS: If deficiency level ≥ 6.4 ng/ml Sample size NS: studies with n ≥ 500; S: if sample size < 500 Country NS: American studies; S: Asian studies Zhang D [ 11 ] 16 studies 5,657/6,557 MTHFR C677T, A1298C, G1793A Overall cancer risk Serum homocysteine S: increased risk with high homocysteine Serum folate S: increased risk with folate deficiency S.Chuang [ 29 ] 8 publications (10 cohorts, representing 3,477 cases/7,039 controls) CRC Serum folate NS: higher levels compared to lowest and risk S: inverse association between circulating folate and CRC risk in studies that used the radioimmunoassay. D.Kennedy [ 30 ] 67 studies met criteria; 62 case controlled, 2 cohort and 3 older versions retained for folate intake data CRC MTHFR polymorphisms S: reduced risk of CRC with high total folate intake with 677TT genotype, 677CC NS: A1298C He H [ ...…”
Section: Methodsmentioning
confidence: 99%
“…Serum levels used to categorize deficiency were different between studies, and some were higher than what is reported in the literature, which may have impacted results. These findings need to be confirmed using consistent cutoffs categorizing deficiency [ 28 ].…”
Section: Methodsmentioning
confidence: 99%